Item, Document, Carrier: An Object Oriented Approach - Manzanos, Norberto (2012)
I discuss the concept of Item as stated by the International Federation of Library Associations and Institutions (IFLA) in the conceptual model Functional Requirements for Bibliographic Records (FRBR) and the object-oriented version of it (FRBR OO). Using objectoriented modeling techniques I analyze the relationship of the Item with the Manifestation entity, the concept of Document, and the physical object as a Carrier of a Content. A class scheme is proposed, not only as an implementation example, but as a way of clarifying some bibliographic concepts as well.